Does CSR Expenditure and Sustainability Reporting Improve Firm Performance? Mandatory CSR Regimes in India - Arunesh Garg; Pradeep Kumar Gupta (Universitas Pasundan, 2021)
This paper aims to investigate whether firms that comply with corporate social responsibility (CSR) expenditure and undertake voluntary sustainability reporting will have lower systematic risk and higher stock returns—the proxies for measuring firm performance—in mandatory CSR regimes in India. The instrumental approach of stakeholder theory asserts that firms considering stakeholders’ interests, including societal interest, are likely to show better firm performance compared to others. Therefore, on the basis of such a theory, this study attempts to link sustainability reporting and CSR compliance with firm performance. One-way Analysis of Variance (ANOVA) and post-hoc tests were used to examine the proposed hypotheses and analyze the results for firms meeting the criteria of CSR provisions and are listed in the National Stock Exchange (NSE) of India. The period of study covers four financial years from 2015–16 to 2018–19, after India mandated CSR expenditure on April 1, 2014. Results reveal that markets value those firms that meet the mandatory CSR expenditure requirement but do not undertake voluntary sustainability reporting. The findings offer important implications for firms, investors, and policymakers of countries, including those that are planning for CSR legislation.